River response to climate and sea level changes during the Late Saalian/Early Eemian in northern Poland – a case study of meandering river deposits in the Chłapowo cliff section - Moskalewicz, Damian; Sokołowski, Robert J.; Fedorowicz, Stanisław (Geologos, 2016)
Fluvial sediments in the Chłapowo cliff section were studied in order to reconstruct their palaeoflow conditions and stratigraphical position. Lithofacies, textural and palaeohydraulic analyses as well as luminescence dating were performed so as to achieve the aim of study. Sedimentary successions were identified as a record of point bar cycles. The fluvial environment probably functioned during the latest Saalian, shortly after the retreat of the Scandinavian Ice Sheet. Discharge outflow was directed to the northwest. The river used the older fluvioglacial valley and probably was directly connected to the Eem Sea. Good preservation and strong aggradation of point-bar cycles were related to a rapid relative base level rise. The meandering river sediments recognised showed responses to climate and sea level changes as illustrated by stratigraphical, morphological and sedimentological features of the strata described. The present study also revealed several insights into proper interpretation of meandering fluvial successions, in which the most important were: specific lithofacies assemblage of GSt (St, Sp) → Sl → SFrc → Fm (SFr) and related architectural elements: channel/sandy bedforms CH/SB → lateral accretion deposits LA → floodplain fines with crevasse splays FF (CS); upward-fining grain size and decreasing content of denser heavy minerals; estimated low-energy flow regime with a mean depth of 1.6–3.3 m, a Froude number of 0.2–0.4 and a sinuosity of 1.5.